(untitled) (Journal of Philosophy Culture and Political Science, 2020)
Elections are an important institution of democracy, and distrust of them can be one of the factors in the crisis of legitimacy. In modern conditions, there are many studies related to trust in political institutions: the institution of the presidency, parliament, political parties, etc. At the same time, the problem of confidence of Kazakhstan citizens in the institution of elections remains poorly understood. Therefore, this article focuses on the causes and factors of Kazakhstan’s distrust of the election institution (economic, political, historical, cultural, organizational factors). A study of the theoretical works of scientists made it possible to reveal the essential content of the category of “trust”, its role and functions in socio-political life. The demand for news resources on the Internet allows us to conclude the need for in-depth study. This topic is of particular relevance, as social networks reflect the attitude of citizens to the policies pursued by public authorities, the political culture and values of the population, and the level of their political participation. With the help of the monitoring program of opinions and references in the information space OMSystem, a large data array was obtained, which made it possible to determine the main reasons for the distrust of Kazakhstan people in the election institution. Key words: election institution, trust, political values, social networks.